Dopamine and Serotonin Metabolism in Hepatic Encephalopathy. Issue 5907 (23rd March 1974) - Knell, A. J.; Davidson, A. R.; Williams, Roger; Kantamaneni, B. D.; Curzon, G.
Abstract : Patients with stupor or coma from fulminant hepatic failure were found to have high cerebrospinal fluid concentrations of homovanillic acid (HVA) and 5-hydroxyindole acetic acid (5-HIAA), metabolites of dopamine and serotonin respectively. Excessive amounts of their precursors—phenylalanine and tyrosine and free tryptophan—were found in the patients' plasma. Methionine, which participates in dopamine degradation, was also much increased. Similar disturbances were found in patients suffering an acute exacerbation of chronic encephalopathy. These abnormalities would be consistent with other evidence of an increased turnover of serotonin and possibly dopamine in the brain during hepatic encephalopathy.